Subclinical atherosclerosis as a risk factor of cardiovascular events - S. A. Boytsov; V. V. Kukharchuk; Yu. A. Karpov; I. V. Sergienko; O. M. Drapkina; A. E. Semenova; S. Zh. Urazalina (Кардиоваскулярная терапия и профилактика, 2012)
Subclinical atherosclerosis is an initial, latent stage of chronic progressing arterial inflammation. Destabilisation of asymptomatic, hemodynamically non-significant atherosclerotic plaques (AP) could lead to myocardial infarction, stroke, or sudden death. Since the assessment of AP stability is problematic in real-world clinical settings, the risk stratification should, at least, account for the presence of subclinical atherosclerosis. In 600 ambulatory patients from the Moscow City Western Administrative Okrug who had low and moderate SCORE-assessed cardiovascular risk levels, the prevalence of AP, based on the duplex carotid ultrasound results, was 59% (n=358). Presently, no standard guidelines exist on cardiovascular risk stratification which would include the assessment of subclinical atherosclerosis, despite the importance of the latter as a prognostic factor. Large clinical studies on prognosis in patients with subclinical atherosclerosis will clarify the role of this parameter as an independent cardiovascular risk factor and facilitate the development of respective clinical recommendations.